Participation in decision‐making about medication: A qualitative analysis of medication adherence. (28th June 2018) - Inder, Maree; Lacey, Cameron; Crowe, Marie
Abstract: Rates of relapse in BD are high with medication nonadherence identified as an important contributor to relapse. Psychopharmacology remains a key component to the treatment of BD; therefore, increased understanding of medication use and ways to promote greater adherence is essential. The aim of the study was to identify how participants with BD experience taking prescribed medication. Participants had BD I or BD II, were users of specialist mental health services, aged 18–64 years, euthymic, mildly hypomanic or depressed, and on any combination of medication. Exclusion criteria were minimal. A semistructured interview was completed exploring patients' views of BD and factors influencing adherence based on the Subjective Experience of Medication Interview. An inductive thematic analysis was used to identify themes. The study participants ( n  = 36) had predominantly bipolar I (78%) and were female (69%), and of New Zealand European ethnicity (67%) with 14% Maori. The mean age was 41 years (SD: 12.0). Findings from the thematic analysis generated three themes: Learning about the clinical meaning of having BD, Understanding how to use medication, and Understanding what works for me. The qualitative nature of our study limits the generalizability of our findings to a broader population of individuals with BD. The participants developed confidence in being in charge of their BD through a process of learning about BD and medication and understanding what this meant for them. The findings support greater emphasis on collaborative approaches that recognize the expertise of the individual with BD and the clinician.